Origin and distribution of ancient Thai pig lineages. (17th January 2021) - Chittavichai, Thanyaporn; Surat, Wunrada; Wetchaphan, Sulak; Poungpan, Supanat; Boonmala, Sukumal; Netmanee, Suppakorn; Auetrakulvit, Prasit; Khunsong, Saritpong; Wattanapituksakul, Athiwat; Shoosongdej, Rasmi; Wonnapinij, Passorn
Abstract: Whether animal domestication in Mainland Southeast Asia (MSEA) developed locally or began with the introduction of domesticated pigs from present‐day China has been discussed at length. This study compared the mitochondrial control region ( mtCR ) sequences of ancient pig samples from various Thai archeological sites to ancient Chinese pigs and modern Asian pigs. Twenty‐one samples (including eight previously reported ones) from six archeological sites located in three areas of Thailand were applied to haplotype analysis along with 2005 sequences of ancient Chinese pigs and modern Asian pigs. The haplotype network showed that genetic diversity and relationship with ancient Chinese pigs suggested multiple origins of ancient Thai maternal lineages, located in present‐day China and MSEA, specifically Thailand. The distinct mtCR haplotypes found in western compared with those found in eastern and central ancient Thai pigs suggested two possible routes of the past migration. These routes corresponded to the movement of agriculturists from present‐day China to MSEA. Several shared haplotypes found between ancient Thai pigs from different archeological sites suggested people contact in the past. Most ancient Thai pigs left their descendants in the contemporary Asian population. Hence, it was proposed that most maternal ancestors of ancient Thai pigs migrated from present‐day Southern China to MSEA via two routes with some local gene flow degrees and left their descendants in Thailand. These results would pave the way for future studies focusing on the history of MSEA pig domestication.